Green Sahara Simulations with iCESM - Tabor, Clay R; Otto-Bliesner, Bette L; Liu, Zhengyu (PANGAEA, 2021)
Files contain monthly climatologies of surface temperature, 2m temperature, sea level pressure, precipitation, and d18O of precipitation from 50-year averages of the preindustrial control, mid-Holocene with desert Sahara, and mid-Holocene with vegetated Sahara experiments discussed in the manuscript.